1991
DOI: 10.1111/j.1600-9657.1991.tb00204.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of sodium perborate preparations used for intracoronal bleaching of discolored non‐vital teeth

Abstract: Bleaching materials containing 30% hydrogen peroxide have been used successfully for the treatment of discolored non-vital teeth. Intracoronal application of these materials was occasionally associated with the development of external root resorption. Extracted human teeth with intact crowns were discolored in vitro and bleached with three preparations of sodium perborate. These preparations included: sodium perborate with 30% hydrogen peroxide, sodium perborate with 3% hydrogen peroxide and sodium perborate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 14 publications
1
41
2
6
Order By: Relevance
“…The mixture comprised sodium perborate and 120 volume hydrogen peroxide mixed to a paste on a sheet of glass (11,12) and was photocatalyzed in situ with a lamp (Illuminator, Union Broach, York, PA) used at 50% heat intensity. In all cases bleaching was accompanied by frequent washing with 5% sodium hypochlorite to potentiate the bleaching effect by liberating nascent oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…The mixture comprised sodium perborate and 120 volume hydrogen peroxide mixed to a paste on a sheet of glass (11,12) and was photocatalyzed in situ with a lamp (Illuminator, Union Broach, York, PA) used at 50% heat intensity. In all cases bleaching was accompanied by frequent washing with 5% sodium hypochlorite to potentiate the bleaching effect by liberating nascent oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…Rotstein et al (61,62) and Weiger et al (63) did not report any significant difference in the effectiveness between sodium perborate mixed with 3%-30% hydrogen peroxide and the sodium perborate-distilled water mixture. However, the whitening effect of the second mixture can take longer, so that more frequent changes of the bleaching agent might be necessary.…”
Section: Comparison Studiesmentioning
confidence: 95%
“…29 In vitro studies have concluded that sodium perborate in water, sodium perborate in 3% and 30% hydrogen peroxide, and 10% carbamide peroxide are all efficient at internal bleaching of non-vital teeth. [30][31][32][33][34] Various heat sources may be applied to speed the reaction and improve the bleaching effect. 35 The medicament is sealed in the pulp chamber for three to seven days, and is thereafter replaced regularly until acceptable lightening is achieved.…”
Section: Chemical Reactions Of Hydrogen Peroxidementioning
confidence: 99%